Additions to the epiphytic macroalgae flora of Bahia and Brazil - Santos, Alana Araujo Dos; Moura, Carlos Wallace Do Nascimento (Phytotaxa, 2011)
The northeastern coast of Brazil is one of the richest and most diverse areas for the marine algae, but there are still many gaps in our knowledge about the flora, especially in terms of deep-water taxa and small epiphytic macroalgae. Studies of the epiphytic algae on Acetabularia crenulata from the coastal waters along the beaches of Barra Grande and Penha, Vera Cruz, Itaparica Island, Bahia State, Brazil, revealed the occurrence of the genus Chroodactylon and the species Chroodactylon ornatum in the South Atlantic Ocean. The red algae Chondria collinsiana and green algae Phaeophila dendroides expanded its geographical distribution to the northeastern coast of Brazil; the green algae Ulva clathrata and U. flexuosa subsp. paradoxa are new records for the coast of Bahia. The vegetative and reproductive structures are described in detail and a comparison with similar species is provided.